2010
DOI: 10.1016/j.febslet.2010.07.033
|View full text |Cite
|
Sign up to set email alerts
|

The Drosophila homolog of methionine sulfoxide reductase A extends lifespan and increases nuclear localization of FOXO

Abstract: a b s t r a c tMethionine sulfoxide reductase A (msrA) was previously found to increase resistance to oxidative stress and longevity in animals. We identified Drosophila msrA (dmsrA), a Drosophila homolog of human msrA, as a downstream effector of forkhead box O (FOXO) signaling in Drosophila, which enhances resistance to oxidative stress and increases survival under stressed conditions. Additionally, overexpression of dmsrA in neurons extended the lifespan of flies. Moreover, overexpression of dmsrA in fat bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
39
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(41 citation statements)
references
References 35 publications
(51 reference statements)
1
39
1
Order By: Relevance
“…Earlier work identified Eip71CD as a cold-responsive gene in two D. virilis groups [29], with expression levels of Eip71CD being consistently lower during acclimation to low temperature. Given that overexpression of Eip71CD also confers resistance to oxidative stress [30], it is possible that its higher expression levels in lsp2>Sdc-IR flies may be the result of an increase in oxidative stress in these flies. The trade-off, however, is an enhanced sensitivity to cold.…”
Section: Resultsmentioning
confidence: 99%
“…Earlier work identified Eip71CD as a cold-responsive gene in two D. virilis groups [29], with expression levels of Eip71CD being consistently lower during acclimation to low temperature. Given that overexpression of Eip71CD also confers resistance to oxidative stress [30], it is possible that its higher expression levels in lsp2>Sdc-IR flies may be the result of an increase in oxidative stress in these flies. The trade-off, however, is an enhanced sensitivity to cold.…”
Section: Resultsmentioning
confidence: 99%
“…The underlying molecular mechanism of MsrA upregulation by AS-IV was explored. A previous study indicated that MsrA expression is regulated via the forkhead box protein/FOXO signaling pathway (30). Sirt1 regulates tyrosine hydroxylase expression and the differentiation of neuroblastoma cells via the FOXO3a signaling pathway (31).…”
Section: As-iv Increases Msra Protein Expression Through the Nad-depementioning
confidence: 99%
“…Thus, MsrA overexpression could change the metabolism of methionine that is important for sulfur and DNA methylation pathways involved in aging (42,43). In addition, a forkhead transcription factor, FOXO3a, directly activates the human MSRA gene (34) and its homologs (DAF16 in Caenorhabditis elegans and dFOXO in fruit fly) activate worm msrA (34) and Drosophila msrA genes (39). FOXO3a transcription factor is known to upregulate the expression of genes involved in oxidative stress response and longevity and down-regulate life-shortening genes.…”
Section: Selenium Is An Important Dietary Micronutrient In Mammalsmentioning
confidence: 99%
“…dFOXO overexpression in the adult fatbody of female fruit flies results in increased lifespan (44). Overexpression of Drosophila MsrA caused dFOXO translocation to the nucleus (39), implying that the prolonged lifespan of MsrA-expressing flies may be due not only to the MsrA role in oxidative stress resistance, but also its role in up-regulation of dFOXO. No transcriptional activation of MSRB genes by FOXO3a or its homologs in different organisms was reported thus far.…”
Section: Selenium Is An Important Dietary Micronutrient In Mammalsmentioning
confidence: 99%